Histopathological Analysis of Lipopolysaccharide-Induced Liver Inflammation and Thrombus Formation in Mice: The Protective Effects of Aspirin - Hayate Saitoh; Miina Sakaguchi; Fumito Miruno; Naoto Muramatsu; Nozomi Ito; Kanako Tadokoro; Kiyoharu Kawakami; Kazuhiko Nakadate (Current Issues in Molecular Biology)
Hepatitis, a significant medical concern owing to its potential to cause acute and chronic liver disease, necessitates early intervention. In this study, we aimed to elucidate the histopathological features of lipopolysaccharide-induced hepatitis in mice, focusing on tissue alterations. The results demonstrated that hepatocytes exhibited decreased eosin staining, indicating cellular shrinkage, whereas sinusoids were swollen with blood cells. Detailed electron microscope analysis identified these blood cells as leukocytes and erythrocytes, which confirmed a thrombus formation within the liver. Pre-treatment with aspirin significantly attenuated these pathological changes, including reductions in inflammatory markers such as C-reactive protein, interleukin-1β, and tumor necrosis factor-alpha. These findings highlight aspirin’s anti-inflammatory and antiplatelet effects in mitigating liver inflammation and thrombus formation. In this study, we highlighted the potential of aspirin as a therapeutic agent for liver inflammation, in addition to providing insights into hepatocyte alterations and sinusoidal blood cell aggregation in liver inflammation. Aspirin, through the protection of endothelial cells and reduction of cytokine levels, may have broader applications in managing liver disease and other systemic inflammatory conditions. This emphasizes its value in prevention and therapy.